DEVELOPING HALAL TRAVEL AND HALAL TOURISM TO PROMOTE ECONOMIC GROWTH: A CONFIRMATORY ANALYSIS - Abrista Devi; Irman Firmansyah (Journal of Islamic Monetary Economics and Finance, 2019)
The purpose of this paper is to identify the factors of various backgrounds in the literature having to do with halal purchase intention of Muslim travellers on halal travel and tourism sector. It also aims to investigate which antecedents, among all, that have the dominant determinants toward the development of halal travel and tourism purchaseintention. A total of 255 respondents originating from several major cities of West Java were involved in random sampling technique to measure their personal perception on the determinant factors of halal purchase intention. Data were collected through structured questionnaire with a five-point Likert scale. The questionnaire has been divided into two main parts, the first part identifies the respondent identity, while the second part provide 6 main sub-part statements on halal awareness, personal societal perception, religious belief, halal marketing, halal travel & tourism, and infrastructure. Confirmatory Factor Analysis (CFA) will be used to acquire the most critical to the least critical indicators in explaining purchase intention on halal travel and tourism industry sector. The paper concludes that most customers rely on halal marketing, making it the dominant determinant factor. Meanwhile, the second dominant determinant is halal travel and tourism. Then, the third determinant is halal awareness. Religious beliefs and personal societal perceptions are the last two priorities. This paper offers a detailed insight into various behaviors of customer’s purchase intention on halal travel and tourism sector as well as delivers a new model of purchase intention through detailed latent-variables. Finally, the relevant stakeholders, in particular government, should enhance the halal marketing on travel and tourism through various programs and activities, such as massive promotion, socialization, and literacy.